顎下部に生じた非脂腺型リンパ腺腫の1例 - 田中, 陽一; 竹川, 政範; 末次, 博; 先川, 信 (日本口腔外科学会雑誌, 2019)
Non-sebaceous lymphadenoma (NSL) is a rare benign salivary gland tumor that is difficult to diagnose preoperatively on the basis of clinical features. We report a case of NSL arising in the left submandibular region in a 66-year-old woman. The patient had complained of a painless mass in the left submandibular region. Her medical history included a left parotidectomy for adenoid cystic carcinoma (ACC) 22 years ago. Computed tomography showed an enhanced mass with the inside low-density at the distal part of the submandibular gland and no residual parotid gland. On the basis of these findings, lymph node metastasis from ACC or a submandibular gland tumor was suspected. The mass was removed with the left submandibular gland under general anesthesia. Histopathologically, the mass was diagnosed as a NSL. There has been no sign of recurrence as of 2 years after the operation.